Vitamin K-3 family members - Part II: Single crystal X-ray structures, temperature-induced packing polymorphism, magneto-structural correlations and probable anti-oncogenic candidature - Rane, Sandhya; Ahmed, Khursheed; Salunke-Gawali, Sunita; Zaware, Santosh B.; Srinivas, D.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Temperature-induced packing polymorphism is observed for vitamin K-3 (menadione, 3-methyl-1,4-naphthoquinone, 1). Form la crystallizes at 300 K and 1b at 277 K both in the same space group P2(1)/c. Form 1b contains one molecule per asymmetric unit, performing anisotropy in g-factor viz. g(z) = 2.0082, g(y) = 2.0055 and g(x) = 2.0025, whereas form 1a contains two molecules in its asymmetric unit. Vitamin K-3 family members 2, [2-hydroxy vitamin K-3] and 3, [2-hydroxy-1-oximino vitamin K-3] also perform intrinsic neutral active naphthosemiquinone valence tautomers even in dark having spin concentrations due to hydrogen bonding and aromatic stacking interactions which are compared to vitamin K-3. The significant lateral C-H center dot center dot center dot O and O-H center dot center dot center dot pi bifurcated or pi-pi(center dot) interactions are discussed for molecular associations and radical formations. X-ray structure of 3 revealed pi-pi(center dot) stack dimers as radicals signatured in PR as triplet with five hyperfine splits [(A) over bar(N-14) = 11.9 G]. The centrosymmetric biradicals in 3 show diamagnetism at high temperature but below 10 K it shows paramagnetism with mu(eff) as 0.19 B.M. Vitamin K-3 and its family members inhibit biological activities of acid phosphatase (APase), which are proportional to their spin concentrations. This may relate to their probable anti-oncogenic candidature in future. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anti-oncogenic candidature; H-bonding; Magneto-structural correlations; Naphthosemiquinones in vitamin K-3 family; Packing polymorphism; Spin concentrations

Role of hydrogen bonding in pseudocapacitance of covalent organic frameworks - Chandra, Suman; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: COF; H-bonding; pseudocapacitance

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus